Organoleptic Test of Herbal Tea Made with Corn Silk (Zea Mays L.), Papaya Seeds (Carica papaya L.) and Dragon Fruit Peels (Hylocereus polyrhizus L.) - Ludfi, Atha Adiwidya; Putri, Frichelle Amelia; Ferris, Keyla Permata; Hartoyo, Azizah Risqi Putri; Ardiansyah, Farel; Bahira, Aliya (Jurnal Biologi Tropis, 2025)
Tea (Camellia sinensis) is one of the most widely consumed beverages globally, valued for its economic, health, and cultural benefits. In Indonesia, abundant natural materials with antioxidant properties, such as dragon fruit peels, corn silk, and papaya seeds, are often discarded as waste. This study aimed to utilize these materials to create teatrasi herbal tea and evaluate its antioxidant and flavonoid content, sensory attributes, and overall acceptability. method and analysis the process involved material preparation, thorough washing, drying at specific temperatures and times, grinding, and packaging. Three formulations were tested, with Formula 3 (40% corn silk, 20% papaya seeds, and 40% dragon fruit peels) being the most favored based on hedonic tests. Antioxidant and flavonoid analyses confirmed strong antioxidant activity (IC50: 89.27 ppm) and high flavonoid content (884.64 mg/L QE) in Formula 3. Results organoleptic tests highlighted its distinctive corn silk aroma, reddish-brown color, and mild flavor. Respondents rated its aroma, color, and taste with favorability levels of 93.75%, 90.62%, and 92.70%, respectively, achieving an overall acceptance rate of 92.29%. Conclusion, this research demonstrates the potential of converting underutilized natural resources into sustainable, health-enhancing beverages.